GAMBARAN KOMITMEN PROFESI DOSEN TETAP UNIVERSITAS “XY” JAKARTA - Epheneta Epheneta; Maria Dwi Yanika Hesti Nugraha; Natasia Natasia (Psibernetika, 2012)
Starting era of globalization and technology, is an era by setting a particular specification for the human resources that give great influence to the world of education. At some universities, especially educational organizations, people or human resources is an important element, in this case is a lecturer. Competency of lecturers will be increased according to increasing faculty commitment to the profession. Therefore, it is important as an educational institution (college) to be able to create the conditions and climate that can strengthen the commitment of profession. Lecturer professional commitment was measured using a questionnaire based on the characteristics of a profession committed lecturer in the opinion of Meyer and Allen (in Bagraim, 2003), the reliability of 0.811. The population were the University of “XY” lecturer. Subjects in this study were drawn from a total of 48 lecturer with a saturation sampling technique (Sugiyono, 2005). This study aims to know the description of the profession's commitment of University of “XY”. Survey data collection method and analyzed by descriptive analysis techniques. The results showed that the profession's commitment lecturer University of “XY” Jakarta is reflected in a positive affective commitment to the profession.Keywords: description of professional commitment, commitment, lecturer profession